2021
DOI: 10.1093/ehjcr/ytab277
|View full text |Cite
|
Sign up to set email alerts
|

His-optimized cardiac resynchronization therapy in a patient with heart failure and right bundle branch block: a case report

Abstract: Background  Cardiac resynchronization therapy (CRT) is an option for treatment for chronic heart failure (HF) associated with left bundle branch block (LBBB). Patients with HF and right bundle branch block (RBBB) have potentially worse outcomes in comparison to LBBB. Traditional CRT in RBBB can increase mortality and HF deterioration rates over native disease progression. His bundle pacing may improve the results of CRT in those patients. Furthermore, atrioventricular node ablation (AVNA) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…In these studies, the superiority of HOT-CRT in terms of providing a shorter right ventricular activation time compared to other resynchronization techniques is remarkable, and in this respect, it is a candidate to be the ideal resynchronization method in patients with RBBB. 37 , 38 For patients with LBBB, it may be reasonable to prefer LOT-CRT, which is a fusion pacing method such as HOT-CRT. As a result of the trials conducted by the international LBBAP collaborative study group, it has been reported that LOT-CRT is a pacing technique that should be tried in patients who did not respond to BVP or whose response was insufficient due to the greater electrical resynchronization provided by LOT-CRT.…”
Section: Current Clinical Practice In Crt Implantationmentioning
confidence: 99%
“…In these studies, the superiority of HOT-CRT in terms of providing a shorter right ventricular activation time compared to other resynchronization techniques is remarkable, and in this respect, it is a candidate to be the ideal resynchronization method in patients with RBBB. 37 , 38 For patients with LBBB, it may be reasonable to prefer LOT-CRT, which is a fusion pacing method such as HOT-CRT. As a result of the trials conducted by the international LBBAP collaborative study group, it has been reported that LOT-CRT is a pacing technique that should be tried in patients who did not respond to BVP or whose response was insufficient due to the greater electrical resynchronization provided by LOT-CRT.…”
Section: Current Clinical Practice In Crt Implantationmentioning
confidence: 99%